Application of Behavioural Economics for Promotion of Environment-friendly Agricultural Practices for Food Security and Enhanced Farm Income - Manikandan, D (Journal of Agricultural Extension Management, 2018)
Over the years the balance between the food production and environmental sustainability is getting skewed towards adverse environmental practices. There is increasing focus on environmental sustainability. There are a number of country specific initiatives to promote environmentally friendly sustainable practices in the form of special schemes, incentivizing best practices in the form of subsidy, premium for organic produce etc. In recent times the application of concepts of behavioural economics in policy design has received the most attention by policy makers globally, to have a positive impact of their citizen behaviour in various walks of life. This article analyzes the utility of behavioural economics concepts in the promotion of environmentally sustainable farming practices.